Penggunaan Teknik Pembelajaran Menarasi Grafik terhadap Keterampilan Menulis Teks Eksplanasi - Hendrisman Hendrisman; Sufia Retti (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to describe the effect of graphic narration learning techniques on writing explanatory texts for class XI students of SMK Negeri 2 Guguak. The method used in this study is a quantitative experiment. The research design used a pretest-posttest control group. Sampling is done using probability sampling (random sample). The results showed that the mean value obtained was 93 with tcount of 4.023 (> ttable = 1.684). In conclusion, there is a significant difference between the explanatory text writing skills using graphic narration learning techniques compared to students taught using conventional methods at SMK Negeri 2 Guguak. Keywords: Writing Skills, Graph Narration Learning Techniques